Ciência, Tecnologia E Inovação: Do Campo À Mesa 2020
DOI: 10.31692/iciagro.2020.0051
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Delivery Systems of Pesticides Active Agents for Agriculture Applications - An Overview

Abstract: Agricultural protection agents used in soil and crops, when applied conventionally, may have their activity impaired against pests and vectors due to their volatilization, photodegradation, leaching, and other unwanted occurrences caused by weather conditions. These problems cause economic and environmental damage due to the high volume of applications necessary for the farmer to achieve the desired results. The indiscriminate use of free pesticides causes high environmental pollution because these compounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
5
0
3
Order By: Relevance
“…Plant-derived nano-pesticides have been tailored for desired properties, involving the use of matrix types [94]. Studies have reported carrier systems prepared by organic and inorganic matrices/polymers and suitable surfactants as a means of delivering various extracts, EO, and their active compounds [88,94].…”
Section: The Role Of Nanotechnology In Plant-derived Pesticide Formul...mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-derived nano-pesticides have been tailored for desired properties, involving the use of matrix types [94]. Studies have reported carrier systems prepared by organic and inorganic matrices/polymers and suitable surfactants as a means of delivering various extracts, EO, and their active compounds [88,94].…”
Section: The Role Of Nanotechnology In Plant-derived Pesticide Formul...mentioning
confidence: 99%
“…Plant-derived nano-pesticides have been tailored for desired properties, involving the use of matrix types [94]. Studies have reported carrier systems prepared by organic and inorganic matrices/polymers and suitable surfactants as a means of delivering various extracts, EO, and their active compounds [88,94]. The utilization of nature/organic matrices' resources matter is growing rapidly to compete with the non-organic matrices, such as chitosan, gum arabic, and zein.…”
Section: The Role Of Nanotechnology In Plant-derived Pesticide Formul...mentioning
confidence: 99%
“…No Brasil e em outros países pelo mundo, pouco ou nada se sabe sobre sistemas de agricultura de commodities como os adotados pela província de Xinjiang, pelo contrário, o uso dos sistemas tradicionais de agricultura só aumentam, e com eles o aumento do desmatamento, do consumo de água e do uso de pesticidas (DA SILVA JÚNIOR et al, 2020a;DE OLIVEIRA et al, 2020). Por isso, é importante que profissionais, estudantes e pesquisadores das áreas ambientais, agronômicas, têxtil e moda tenham o conhecimento dessas informações e se tornem precursores de uma nova mentalidade local.…”
Section: Resultsunclassified
“…Os recursos florestais que podem contribuir para uma indústria têxtil mais sustentável vão além dos corantes naturais, de novas modalidades de cultivo/agricultura e novas alternativas de fibras vegetais; podem inclusive, fornecer insumos para a produção de nanoestruturas obtidas por síntese verde que servem como suporte de compostos pesticidas e fertilizantes. Nanopesticidas e nanofertilizantes são capazes de otimizar a entrega e distribuição dos compostos ativos de forma controlada nas plantas e nas lavouras, o que aumenta a eficácia do controle de pragas e reduz a carga desses produtos aplicados, como mostra os trabalhos de Da Silva Júnior et al ( 2020a) e De Oliveira et al ( 2020). Vários suportes nanométricos podem ser usados para o carregamento e entrega controlada de agroquímicos na lavoura, mas um em especial, obtido a partir de biomassa (frutas, folhas, caules, etc.)…”
Section: Resultsunclassified
See 1 more Smart Citation